2013
DOI: 10.4018/ijitpm.2013100106
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Project Management Certification on the Triple Constraint

Abstract: This research paper describes key information technology (IT) project management activities in terms of project scope, time, and cost management, namely the triple constraint. The authors contend that the ability to properly manage and execute these activities is the quintessential component that oftentimes drives whether projects succeed or fail. The literature shows that IT projects have a dismal success rate but successful projects have been on the rise. The authors attempt to determine if the increase of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…As expected, the study found no link between a commercial PM certification and project efficiency. The study confirms the findings of previous quantitative studies (Abu-rumman, 2014;Catanio et al, 2013;Nazeer & Marnewick, 2018;Quan & Cha, 2010;Robertson, 2015;Starkweather & Stevenson, 2011). This study adds to the growing body of evidence that commercial PM certifications do not impact project efficiency.…”
Section: Conclusion Based On the Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As expected, the study found no link between a commercial PM certification and project efficiency. The study confirms the findings of previous quantitative studies (Abu-rumman, 2014;Catanio et al, 2013;Nazeer & Marnewick, 2018;Quan & Cha, 2010;Robertson, 2015;Starkweather & Stevenson, 2011). This study adds to the growing body of evidence that commercial PM certifications do not impact project efficiency.…”
Section: Conclusion Based On the Resultssupporting
confidence: 89%
“…Orchestrating the entire project demands a significantly different skill set than providing technical leadership. Lack of project management skills contributes to IT project failure (Carvalho & Rabechini, 2015;Catanio et al, 2013;Rivera-Ruiz & Ferrer-Moreno, 2015).…”
Section: Pm Education and Training Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a survey of IT project managers and the outcome of their projects, Joseph and Marnewick (2017) indicated when a project manager was in possession of professional certification of PMI, there was no associated improvement in successful project outcomes in terms of time, cost and quality. Likewise, Catanio, Armstrong and Tucker (2013) found that the certifications have not made the activities of project managers in project scope management, project time management and project cost management more effective. In addition, Tucker (2013) argues that the formal training and certification cannot lead to better conduct, due to the changing environments that application of knowledge and skills in project management face.…”
Section: Discussion: Similarities and Differences In Professionalisinmentioning
confidence: 99%